A study on retired athletes` training policy optimization based on the career transitions - Zou, D.; Xing, T.; Jiang, C. (2020 Chinese Control And Decision Conference (CCDC) 22.-24.8.2020, 2020)
Professional transformation of athletes is an important institutional arrangement to ensure the long-term interests of athletes and realize sustainable livelihood. The satisfaction of athletes to the training of professional transformation is an important basis for improving the policy of professional transformation of athletes. According to the theory of professional transformation, based on the survey data of athletes' vocational transformation training, this paper constructs a Logistic model to study the influencing factors of satisfaction of athletes' vocational transformation training. The results show that the age of retired athletes, sports level, industry and sports related degree, work adaptability, skill adaptability and monthly average income level have significant impacts on career change satisfaction. In view of the diversified characteristics of the influencing factors of the satisfaction degree of professional transformation, the training contents of professional transformation of athletes should be determined based on the market demand, give full play to the supporting role of social forces and establish a diversified service mechanism for professional transformation of athletes, establish a perfect evaluation mechanism of athletes' vocational transformation training project, continuously improve the standardized level of professional transformation training for athletes, improve the social security system of retired athletes, promote the smooth realization of professional transformation of athletes